The Luminous Darkness of Silence in the Poetics of Simone Weil and Georges Rouault - Caranfa, Angelo (Philosophy & theology, 2011)
This essay tries to demonstrate two distinct but complementary visions to a central theme of Christian faith: humanity’s redemption in the crucified Christ. It will attempt to show how the poetics of Simone Weil (1909–1943) and the poetic art of Georges Rouault (1871–1943) embody different understandings of Christian faith. Considering faith from a philosophical approach, Weil detaches the sufferings of Christ from the totality of salvific history. Viewing faith from the artistic approach, Rouault places the crucified Christ in the context of the history of salvation, including Mary and the Church. Though different from one another, these two visions reveal to us a light in the midst of our dark or suffering existence that makes audible or perceptible the silence of God’s love in Christ that is its source.